Characterization of viscoelastic bending stiffness of uncured carbon-epoxy prepreg slit tape. (1st November 2021) - Rajan, Sreehari; Sutton, Michael A; Wehbe, Roudy; Gurdal, Zafer; Kidane, Addis; Emri, Igor
Highlights: Viscoelastic behavior of uncured tows determined experimentally in relevant temperature range. Measurements show tow obeys time temperature superposition principle (TTSP) WLF and Arrhenius models are excellent fits to data. TTSP for WLF model provide results over 9 decades of time. Data shows tow is elastic during wrinkle formation in AFP manufacturing of thermoset composite components. Abstract: In support of computational modeling of tow placement at elevated temperature, the creep response of IM7/8552 uncured prepreg slit tape material during 3-point bend loading at different temperatures is measured using an RSA III dynamic mechanical analyzer. Short term creep experiments were conducted for a duration of 1000 s at ten different temperatures ranging from −5°C (below Tg of 0 °C) to 40 °C, with the latter being the nominal processing temperature for the tow. Results show that the tow material obeys the time-temperature superposition principle (TTSP) in the temperature range selected for the creep experiments. Using the TTSP, creep compliance master curve spanning more than eight logarithmic decades is obtained for the nominal processing temperature of 40 °C. The time–temperature shift factor is observed to follow closely the William-Landel-Ferry (WLF) model, with the WLF parameters obtained by least square fitting of the experimentally determined shift factors utilizing closed form shifting algorithm (CFS). The WLF model for the material is used to extend the master curve to a range of temperatures above glass transition temperature (Tg ) of the material. The creep compliance data is further employed to obtain the retardation spectra of the material using an algorithm based on the work of a co-author and applied recently to a different material system by the authors. Details for extraction of the retardation spectra from the creep compliance results are provided. Results from these studies demonstrate that the creep compliance reconstructed from the retardation spectra accurately represent the experimental results while providing baseline data to quantify the importance of viscoelastic behavior in wrinkle formation during advanced manufacturing of aerospace components.